Impacts of common components in multistage production system under uncertain conditions - Wazed, M.A.; Ahmed, Shamsuddin; Yusoff, Nukman (2010)
The work desires: i) to determine the optimum level of batch size in bottleneck facility and ii) to analyze the effect of common components on work-in-process (WIP) level and cycle time in a multistage production system under uncertainties. The uncertainty is created by machine breakdown and quality variation. Few simulation models are developed based on a live case from a company. The models are verified and validated with the historical data from the company and by face validity. Taguchi approach for orthogonal array is used in designing experiments and these are executed in WITNESS. It is observed that the variation in level of common component in the system has significant impact on the production WIP level and cycle time. The main contribution of this research is determination of the optimal level of batch size in a bottleneck resource under the uncertainties. This approach can be generalized to any multistage production system, regardless of the precedence relationships among the various production stages in the system.